Social connectedness, optimism, and adaptive coping among university students in mainland China: a mediation model of perceived social support - Fu, Wen (Frontiers in Psychology, 2025)
IntroductionThis mixed-methods study investigated the interplay among social connectedness, optimism, and perceived social support in predicting adaptive coping in university students in mainland China. The study examined the mediating role of perceived social support in the relationships of social connectedness and optimism with adaptive coping.MethodsUsing an explanatory sequential design, quantitative data were first collected from 463 undergraduate students across three universities using questionnaires, and the hypothesized mediation model was tested using path analysis with structural equation modeling (SEM). Subsequently, qualitative data were gathered through semi-structured interviews with 20 students to explain the quantitative findings.ResultsQuantitative results revealed that the hypothesized model showed a good fit to the data. Social connectedness and optimism were significant positive predictors of perceived social support and adaptive coping. Importantly, perceived social support significantly partially mediated the relationships of both social connectedness and optimism with adaptive coping. Qualitative findings contextualized these results, illustrating plausible mechanisms for the mediation pathways, while analysis of contradictory cases highlighted complexities such as optimism facilitating direct intrapersonal coping and pessimism potentially inhibiting support activation.DiscussionThe study’s findings indicate that perceived social support plays a crucial, though not exclusive, mediating role associated with adaptive coping, through which social connectedness and optimism appear to exert some of their positive influences. These findings highlight the importance of fostering social support networks within universities to enhance student well-being and adaptive coping abilities.